Biliary Ablation for Sectoral Duct Injury to Avoid Surgery - Almamoon I. Justaniah; Sami Boshnaq (The Arab Journal of Interventional Radiology, 2024)
Bile duct injury is a common and serious complication of both laparoscopic and open cholecystectomy. The conventional treatment for isolated bile duct injury is hepaticojejunostomy or hepatectomy. We present a case of biliary leak from an isolated right posterior sectoral duct after cholecystectomy treated with percutaneous sclerotherapy using alcohol. Approval and consent waiver were obtained from the Institutional Review Board (IRB 2023-CR-18).